Intelligent Assistance in Authoring Dynamically Generated Web Interfaces - Macias, Jose A (World wide web (Bussum), 2008)
Since its emergence in the early 1990s, the WWW has become not only an information system of unprecedented size, but a universal platform for the development of services and applications. However, most of the advances in web technologies are intended for professional developers, paying poor attention to end-users with no programming abilities but with explicit needs of creating and customizing web-based presentations. This provides a strong motivation for end-users to act as designers at some point, leading to an emerging role of new computing-related professionals to be considered. This paper is an effort to leverage such difficulties by providing intelligent mechanism to assist end-users in web-based authoring tasks. To carry out such a challenge, intelligent user-monitoring techniques are exploited to obtain high-level information that will be used to infer the user’s preferences and assist him throughout the interaction. Furthermore, we report on how iteration patterns can be applied to avoid repetitive tasks that are automatically carried out on behalf of the user. In order to bring off a feasible trade-off between expressivity and ease of use, a user experiment to obtain the user’s perception and evaluate the hit-rate of our system is also presented.